Methyl-Donor and Cofactor Nutrient Intakes in the First 2–3 Years and Global DNA Methylation at Age 4: A Prospective Cohort Study - Taylor, Rachael M. (Nutrients, 2018)
Background: During the early postnatal period, the impact of nutrition on DNA methylation has not been well studied in humans. The aim was to quantify the relationship between one-carbon metabolism nutrient intake during the first three years of life and global DNA methylation levels at four years. Design: Childhood dietary intake was assessed using infant feeding questionnaires, food frequency questionnaires, 4-day weighed food records and 24-h food records. The dietary records were used to estimate the intake of methionine, folate, vitamins B2, B6 and B12 and choline. The accumulative nutrient intake specific rank from three months to three years of age was used for analysis. Global DNA methylation (%5-methyl cytosines (%5-mC)) was measured in buccal cells at four years of age, using an enzyme-linked immunosorbent assay (ELISA) commercial kit. Linear regression models were used to quantify the statistical relationships. Results: Data were collected from 73 children recruited from the Women and their Children’s Health (WATCH) study. No association was found between one-carbon metabolism nutrient intake and global DNA methylation levels (P 0.05). Global DNA methylation levels in males were significantly higher than in females (median %5-mC: 1.82 vs. 1.03, males and females respectively, (P 0.05)). Conclusion: No association was found between the intake of one-carbon metabolism nutrients during the early postnatal period and global DNA methylation levels at age four years. Higher global DNA methylation levels in males warrants further investigation.